Transmitting Renewable Energy to the Grid - Madrigal, Marcelino; Jordan, Rhonda Lenai (World Bank, Washington, DC, 2014)
Many countries are scaling up their investments in renewable energy. In 2010, electricity production from renewable sources - wind, solar, biomass, biofuels, geothermal, hydropower, and ocean energy accounted for 18 percent of global electricity supply. By early 2011, renewables made up a quarter of all installed power capacity. One of the main obstacles to the scale-up of renewable energy is connecting generating sites to the grid in an efficient manner. Renewable energy places greater demands on the transmission network than do conventional energy sources. First, the richest sites for solar and wind energy is often spread across multiple locations far from consumption centers or existing transmission networks. Second, generation is subject to variability in climate conditions (such as wind speed and solar radiation). This note focuses on the transmission implications of the dispersion of renewable energy sources, rather than on the implications of variability. In some sub regions of the United States and countries in Europe that are pursuing renewable energy options, the requirements for investment in transmission already approved by regulators (or forecasted by transmission companies) are double or quadruple recent investment trends. In Brazil the investment needs for renewable energy in some regions surpass the asset value of the distribution utilities closest to the renewable sites.